2020
DOI: 10.1182/bloodadvances.2020003065
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma levels of syndecan-1 and soluble thrombomodulin predict adverse outcomes in thrombotic thrombocytopenic purpura

Abstract: Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a potentially fatal blood disorder resulting from acquired deficiency of plasma ADAMTS13 activity. Despite recent advances in early diagnosis and novel therapeutics, the mortality rate of acute iTTP remains as high as 10% to 20%. Moreover, a reliable clinical and laboratory parameter that predicts disease severity and outcomes is lacking. We show in the present study that plasma levels of syndecan-1 (Sdc-1) and soluble thrombomodulin (sTM) on admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
7
1
Order By: Relevance
“…Despite the relatively small difference in syndecan-1 and sTM between sex-matched and sex-mismatched groups, a recent study has related such relatively minor changes to disease severity [34]. In addition, all of the changes noted in the current study pointed towards the same direction, which is endothelial activation associated with sex-mismatched transfusions.…”
Section: Discussioncontrasting
confidence: 58%
“…Despite the relatively small difference in syndecan-1 and sTM between sex-matched and sex-mismatched groups, a recent study has related such relatively minor changes to disease severity [34]. In addition, all of the changes noted in the current study pointed towards the same direction, which is endothelial activation associated with sex-mismatched transfusions.…”
Section: Discussioncontrasting
confidence: 58%
“…[61][62][63] In the context of COVID-19, impaired MERTK signaling has been proposed as a link between the hyperinflammatory and hypercoagulative state observed in patients with severe disease. 61,[86][87][88] In the model proposed by Lemke et al, sequestration of MERTK-ligand protein spike (S) by developing blood clots results in impaired MERTK signaling in neighboring macrophages and increased pro-inflammatory cytokine production. 61 Sequestration of protein S by sMERTK may also contribute to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Through its role in both endothelial integrity in the lung and immunoregulation, dysregulated MERTK could potentially be a central player in the development of severe COVID-19. In addition, MERTK also plays a role in platelet aggregation (Sather et al, 2007), and its observed higher plasma levels in patients with the severe disease together with increased plasma levels of other proteins involved in hemostasis (Hrycek and Cieslik, 2012; Ikeda et al, 2018; Lu et al, 2020a) suggests an increased risk for coagulation and thrombosis. Coagulopathy and thrombosis have been observed in many patients that presented with severe COVID-19 (Gao et al, 2020; Levi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%